2000
DOI: 10.1159/000026436
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Interleukin-1-Beta Levels after Acute and Prolonged Exposure to Low Temperatures: Human and Rat Studies

Abstract: In this study we have investigated whether IL-1 acts as a mediator of stress responses elicited by exposure to low temperatures. We also sought whether IL-1 is released from the adrenal gland under basal conditions or after exposure to low temperatures. Normal and adrenalectomized (ADX) rats were used for acute studies, whereas the effects of a prolonged exposure were investigated in a group of human subjects during a 45-day stay in Antarctica. Circulating levels of interleukin-1β (IL-1β) were taken as a marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
3
1
Order By: Relevance
“…Shearer et al [2] (2002) reported increased proinflammatory cytokines in winter expeditioners, which is in agreement with our study. In contrast to our findings, an Italian study showed a marked decrease in serum cytokine levels in human subjects after prolonged exposure to a cold environment [9] . Shirai et al [3] have reported that exposure to an Antarctic winter induced a dramatic decrease in the levels of TNF-␣ , IL-1Ra, IL-6 and IL-1 ␤ in serum samples.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Shearer et al [2] (2002) reported increased proinflammatory cytokines in winter expeditioners, which is in agreement with our study. In contrast to our findings, an Italian study showed a marked decrease in serum cytokine levels in human subjects after prolonged exposure to a cold environment [9] . Shirai et al [3] have reported that exposure to an Antarctic winter induced a dramatic decrease in the levels of TNF-␣ , IL-1Ra, IL-6 and IL-1 ␤ in serum samples.…”
Section: Discussioncontrasting
confidence: 99%
“…A typical monocytosis was detected and a striking reduction in the proinflammatory cytokine was noted [7]. Decreased serum levels of IL-10, IL-6, IL-1 receptor antagonist [8] and IL-1β were detected [9]. It has been recognized that cold stress affects various aspects of both cellular and humoral immunity in experimental animals: it decreases lymphocyte proliferation, natural killer cell count and cytolytic activity; it activates complement and induces heatshock proteins [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has reported that cold exposure stimulates the sympathetic nervous system (SNS) to promote BAT activation, which in turn affects glucose and lipid metabolism [32]. In fact, previous studies have found that under conditions of physiological stress, such as cold exposure, the in vivo cytokine levels (IL-1ß) increase [33]. The reason for the increase in cytokine levels in response to stress is not clear, but it may be caused by an increase in the levels of stress hormones such as adrenaline.…”
Section: Discussionmentioning
confidence: 99%
“…The free androgen index (FAI) was calculated as FAI = [testosterone (TEST)/sex-hormone binding globulin (SHBG)] × 100 [32]. Body adiposity index (BAI) was calculated as BAI = hip circumference/height 1.5 − 18 [33]. Visceral adiposity index (VAI) = waist circumference (WC)/(36.58 + 1.89 ×BMI) × tri-glyceride (TG)/0.81 × 1.52/high-density lipoprotein cholesterol (HDL-C) [34].…”
Section: Calculation and Statistical Analysismentioning
confidence: 99%